Kendala Pengembangan Ternak Kerbau di Kecamatan Koto VII Kabupaten Sijunjung - Suparno, Tomi; Maiyontoni, Maiyontoni; Elisia, Rini; Komala, Refika (Lembaga Yasin AlSys, 2025)
The buffalo livestock population in Koto VII Subdistrict, Sijunjung Regency, has experienced a decline due to reduced grazing land and various other constraints hindering its development. This study aims to examine the population structure of buffalo livestock and identify the main challenges faced in its development. A census method was used, involving all 108 buffalo farmers in the area as respondents. Data were collected through a structured questionnaire and analyzed descriptively using numerical tabulation and percentages. The results show a total buffalo population of 755, with a composition of 28% male and 72% female, and an age distribution indicating strong potential for population growth. However, several major constraints were identified, including reduced availability of grazing land due to land-use conversion (64%), low interest among younger generations in livestock farming (25%), and challenges in managing livestock diseases (11%). The findings conclude that while the current population structure in Koto VII Subdistrict supports development efforts, its sustainability heavily depends on the sustainable management of grazing land and increased youth participation in the livestock sector.